Bank Capital and Value in the Cross-Section - Mehran, Hamid; Thakor, Anjan (Review of Financial Studies, 2011)
We develop a dynamic model of bank capital structure in an acquisitions context which predicts: (i) total bank value and the bank's equity capital are positively correlated in the cross-section, and (ii) the various components of bank value are also positively cross-sectionally related to bank capital. Our empirical tests provide strong support for these predictions. The results are robust to a variety of alternative explanations–growth prospects, desire to acquire toe-hold positions, desire of capital-starved acquirers to buy capital-rich targets, market timing, pecking order, the effect of banks with binding capital requirements, Too Big To Fail, target profitability, risk, and mechanical effects. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.